Systematic Literature Review (SLR): Implementasi Sistim Kompensasi dan Penghargaan Terhadap Kinerja Guru SD Muhammadiyah Sidoarjo - Raden Soebiartika; Ida Rindaningsih (Yayasan Literasi Sains Indonesia, 2023)
The development of Muhammadiyah Sidoarjo Elementary School has been very good since 2005 until now. Every year the trust given by the community is getting bigger. This can be seen from the increasing graph of new student admissions from year to year, in which initially, the number of students was only in the range of dozens in each Force. Currently, there are hundreds of students divided into four classes at each level. This great trust in SD Muhammadiyah must be accompanied by the availability of reliable and good quality teachers and employees, who show increasing performance and productivity, so the institution must pay attention to what their needs and desires are so that they can produce high performance and productivity. Generally, an employee wherever they work, the most desirable thing is that they get proper compensation and rewards from the institution where they work and work. The compensation and reward system the main factor that can improve performance, in addition to the factor that works is one of the values of worship in the eyes of Allah. Based on the above description, the author conducted this research to find out the extent to which the implementation of compensation and rewards was able to improve the performance of teachers and employees. For this reason, the author conducted research using the SLR (Systemic Literature Research) method on various literatures by connecting to the actual reality of the implementation of the compensation system, awards on the performance of GUKAR at SD Muhammadiyah Sidoarjo.